Spinoza on miracles and natural laws - Yu Aurora (Belgrade Philosophical Annual, 2024)
Spinoza's philosophy presents a radical reinterpretation of miracles and laws, rejecting traditional views of miracles as breaches in the natural order. This paper argues that for Spinoza, natural law, which directly follows from God, governs the universe with necessity, while civil and physical laws are human inventions. Some events are considered miracles because they contradict the latter laws due to people's ignorance of the true causes. By analyzing Spinoza's typology of laws and his views on extension, I contend that physical laws depend on human imagination and thus cannot be equated with natural law. The paper examines Spinoza's rejection of miracles as supernatural events, demonstrating how they instead reveal the limits of human understanding of natural causality. This study reconciles Spinoza's rationalist commitments with his critique of human cognition's capacity to represent the divine. This rethinking of laws and miracles offers new insights into Spinoza's metaphysics and its implications for his philosophy of science and theology.